FEMALE STEREOTYPE IN BEAUTY PRODUCT ADVERTISMENTS IN ‘GO-GIRL’ MAGAZINE - PRAVITASARI, AMELIA (Jurnal Ilmiah Mahasiswa FIB, 2015)
Keywords: Critical Discourse Analysis, Stereotype, Advertisement, „Go-girl‟magazine.The concept of gender is related with the socio-cultural construction about how men and women should behave. That expectation shapes the stereotypes on the way with how group of people labelled other people. Furthermore, the conventions of gender and stereotypes have been shaped by the discourse practice in the advertisement. This research is intended to find the meaning construction of female stereotype especially in ‘Go-girl’ magazine beauty product advertisement. The object ives are: (1) to find out the lexical choices stereotyping women in ‘Gogirl’ magazine beauty products advertisement (2) to describe the meaning construction about female based on the reader interpretation. This CDA research uses three dimensions of discourse proposed by Norman Fairclough which cover textual analysis, discursive practice and socio-cultural practice.In text analysis level this study suggests that (1) there are two dictions related withwomen personality. (2) there are nine dictions related with physical appearance.Those dict ions result two stereotypes: ‘women should have self confidence andexpressive personalit y’ and ‘women should have good physical appearance’. Inthe discursive level this study suggests that the readers construct the meaning ofadvert isement based on their interpretation, (1) ‘women should have br ight skinand have slim body’ and (2) ‘good personalit y is also important for women’. Inthe socio-cultural practice level, the participants feel that advertisement mayinfluence the reader’s mind but they still have their own concept of beauty.In the future, it is  suggested to the next researcher to develop and explore thistopic more deeply in different theory or object such as newspaper, political propagandas, official documents, law and regulation and so on. So, it will be veryuseful for the knowledge development especially in critical discourse analysis.